Business school capital and study choices in undergraduate education: A student-centred approach. Issue 2 (July 2022) - Ashiru, Folajimi; Whitfield, Ian; Warwick, Philip
Abstract: Relying on the resource-based view and drawing on the work of Pierre Bourdieu and his key concepts of field, habitus and capitals, we scrutinise via student focus group reports, the perceptions of first year business undergraduate students, asking them what university and business school attributes they considered during the application process so that we can determine what attributes give business schools a competitive advantage. Our findings reveal the combination of attributes, what we call symbolic capital, that are essential to attract students to a UK based business school in a research-intensive Russell Group university. This combination of attributes and resources is critical to maintaining the position of a university and business school in the perceptions of applicants. Hence, we refer to the combination of factors as 'Business School Capital'. Highlights: Competition between universities, and in particular business schools, to recruit students is increasing. We identify what are the most prominent attributes and resources which prompted students to choose to study at a UK research intensive university. Rank and university reputation are the most important issues for all student groups. Location, learning environment and language of instruction are also important for many. Students use university rankings as a proxy measure for teaching quality and student satisfaction.